Infeksi Saluran Kemih Sebagai Faktor Resiko Terjadi Gagal Ginjal Kronik Stadium V: Study Kasus - Amirudin; I Made Sumariana (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2024)
Urinary tract infection (UTI) is an infection that attacks the urinary tract, which includes the ureters, bladder, urethra, kidneys, with symptoms such as frequent urination, dysuria, and pain. Most people think that UTI is a common disease so there is no need to treat it completely, even though the bacteria present cause a decrease in the urinary tract defense system due to obstruction in the urinary tract which causes damage to the kidney structure and becomes chronic kidney disease (CKD). This study is a case report of a 29 years old woman who had the main complaint of nausea and vomiting since 10 days ago before being admitted to hospital accompanied by complaints of low back pain, foamy urine for a long time, history of previous illness, history of UTI (+), incomplete antibiotic treatment. From the physical examination, the patient appeared to be in moderate pain, anemic conjunctiva, epigastric tenderness (+), knocking pain in the right and left CVA (+), edema in the extremities. Upper abdominal ultrasound examination showed the impression of bilateral chronic renal disease. It is important to use antibiotics in UTI cases completely, to minimize the occurrence of complications such as CKD. Treatment for UTIs is generally given antibiotics, but if complications develop into end-stage CKD, hemodialysis therapy can be given as well as a special diet and blood pressure control.